2001
DOI: 10.1177/002215540104900404
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin Distribution and the Actomyosin Cytoskeleton in Toxoplasma gondii

Abstract: S U M M A R YThe gliding motility of the protozoan parasite Toxoplasma gondii and its invasion of cells are powered by an actin-myosin motor. We have studied the spatial distribution and relationship between these two cytoskeleton proteins and calmodulin (CaM), the Ca 2 ϩ -dependent protein involved in invasion by T. gondii. A 3D reconstruction using labeling and tomographic studies showed that actin was present as a V-like structure in the conoidal part of the parasite. The myosin distribution overlapped that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…14). It is therefore noteworthy that recent immunofluorescence studies of the calmodulin-actomyosin complex in intracellular T. gondii disclose an apically focused pattern very similar to that found for the V-PPase in this study (46) and that earlier studies demonstrated an anteriorally displaced concentration of intracellular Ca 2ϩ within unidentified compartments, possibly acidocalcisomes, in the same organism (47). Knowing that microneme discharge, one of the first events in host cell invasion, requires the mobilization of intracellular Ca 2ϩ stores (48), it is conceivable that acidocalcisomes serve as a source of this Ca 2ϩ .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…14). It is therefore noteworthy that recent immunofluorescence studies of the calmodulin-actomyosin complex in intracellular T. gondii disclose an apically focused pattern very similar to that found for the V-PPase in this study (46) and that earlier studies demonstrated an anteriorally displaced concentration of intracellular Ca 2ϩ within unidentified compartments, possibly acidocalcisomes, in the same organism (47). Knowing that microneme discharge, one of the first events in host cell invasion, requires the mobilization of intracellular Ca 2ϩ stores (48), it is conceivable that acidocalcisomes serve as a source of this Ca 2ϩ .…”
Section: Discussionsupporting
confidence: 87%
“…Knowing that microneme discharge, one of the first events in host cell invasion, requires the mobilization of intracellular Ca 2ϩ stores (48), it is conceivable that acidocalcisomes serve as a source of this Ca 2ϩ . Acidocalcisomes may thereby provide the Ca 2ϩ required for activating the calmodulin-dependent myosin light chain kinases that regulate the actomyosin motor that governs parasite motility and host cell invasion (46). If this were the case, the V-PPase would provide the motive force for acidocalcisomal Ca 2ϩ accumulation by H ϩ /Ca 2ϩ antiport.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between passively forced conoid extrusion and infectivity of T. gondii would be investigated. The actin and myosin filaments that influence the motilities of tachyzoites are also located at the apical pole, and calmodulin is located at the anterior region of T. gondii tachyzoites during the extracellular state (Pezzella-D'Alessandro et al, 2001). In our experiment, calmodulin and actin were observed at the anterior end of tachyzoites (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Conoid extrusion induced by Ca 2+ ionophores can be inhibited by CD, indicating a participation of actin filaments (Mondragón and Frixione, 1996). Previous studies have shown actin localized at the apical end (Yasuda et al, 1988;Pezzella-D'Alessandro et al, 2001) and as part of the subpellicular network (Patrón et al, 2005). As the conoid is directly related to the subpellicular network cytoskeleton (Nichols and Chiappino, 1987;Patrón et al, 2005), it was reasonable for us to evaluate the role of cytoskeleton proteins under the conoid extrusion induced by ethanol.…”
Section: +mentioning
confidence: 97%